Accounting for Optical Generation in the Quasi-Neutral Regions of Perovskite Solar Cells - Parnian Ferdowsi; Farzan Jazaeri; Efrain Ochoa-Martinez; Jovana V. Milic; Michael Saliba; Ullrich Steiner; Jean-Michel Sallese (IEEE Journal of the Electron Devices Society, 2022)
Predicting the performance of solar cells though analytical models is important for the theory-guided optimization of these devices. Earlier models neglect the impact of the optical generation in the quasi-neutral regions of a perovskite solar cell. Here, a new model is developed that takes optical generation in these regions into account. The model includes the full depletion approximation and the drift-diffusion transport mechanisms. A comparison with earlier models demonstrates the improved predictive power of the developed model. In addition, the accuracy of the model was assessed by comparing it prediction to experimental data obtained from working devices.